FastM: Design and Evaluation of a Fast Mobility Mechanism for Wireless Mesh Networks - Couto, Luís (2012)
Although there is a large volume of work in the literature in terms of mobility approaches for Wireless Mesh Networks, usually these approaches introduce high latency in the handover process and do not support realtime services and applications. Moreover, mobility is decoupled from routing, which leads to inefficiency to both mobility and routing approaches with respect to mobility. In this paper we present a new extension to proactive routing protocols using a fast mobility extension, FastM, with the purpose of increasing handover performance in Wireless Mesh Networks. With this new extension, a new concept is created to integrate information between neighbor wireless mesh routers, managing locations of clients associated to wireless mesh routers in a certain neighborhood, and avoiding packet loss during handover. The proposed mobility approach is able to optimize the handover process without imposing any modifications to the current IEE 802.11 MAC protocol and use unmodified clients. Results show the improved efficiency of the proposed scheme: metrics such as disconnection time, throughput, packet loss and control overhead are largely improved when compared to previous approaches. Moreover, these conclusions apply to mobility scenarios, although mobility decreases the performance of the handover approach, as expected.